1999
DOI: 10.1037/0022-3514.76.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatized sources and persuasion: Prejudice as a determinant of argument scrutiny.

Abstract: Two experiments examined the viability of several explanations for why majority group individuals process persuasive messages from stigmatized sources more than those from nonstigmatized sources. In each study, majority group participants who either were high or low in prejudice or were high or low in ambivalence toward a stigmatized source's group were exposed to a persuasive communication attributed to a stigmatized (Black, Experiment 1; homosexual, Experiment 2) or nonstigmatized (White, Experiment 1; heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 50 publications
4
77
1
Order By: Relevance
“…Indeed, overweight individuals who stereotype others in their group may be particularly persuasive to outgroup members, since stigmatized sources are more motivating than non-stigmatized sources in prompting majority group members to examine a particular message. 19 Somewhat surprisingly, the strength of this anti-fat bias did not differ significantly by ethnicity, although the trend was in the predicted direction, with African Americans holding a less strong bias compared to Caucasians. A clear limitation in this study, however, was the sample size, which might not have provided sufficient power to detect ethnic differences.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, overweight individuals who stereotype others in their group may be particularly persuasive to outgroup members, since stigmatized sources are more motivating than non-stigmatized sources in prompting majority group members to examine a particular message. 19 Somewhat surprisingly, the strength of this anti-fat bias did not differ significantly by ethnicity, although the trend was in the predicted direction, with African Americans holding a less strong bias compared to Caucasians. A clear limitation in this study, however, was the sample size, which might not have provided sufficient power to detect ethnic differences.…”
Section: Discussionmentioning
confidence: 92%
“…Alternatively, the female advantage in the low-complexity condition may be the result of participants processing the testimony presented by the female expert, compared to her male counterpart, more deeply. Along these lines, White and his colleagues (White & Harkins, 1994) found that individuals, particularly those low in prejudice (Petty, Fleming, & White, 1999), were more likely to process a message more carefully when it was presented by a stigmatized as opposed to a nonstigmatized source (e.g., Blacks as opposed to Whites, homosexual as opposed to heterosexual). Thus, it is possible that in an effort to guard against biases and prejudices that could color their evaluation of the female expert, participants may have scrutinized the message from the female expert more carefully and thoroughly than the information presented by her male counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…attributed to factors other than racist attitudes). There are clear similarities between racism and sexism (Fiske & Taylor, 1991;Swim et al, 1995;Tougas et al, 1995), which makes it possible to apply this theory to the latter (Petty, Fleming, & White, 1999). We therefore predict that people with more traditional attitudes to male gender roles will be motivated to appear non-prejudiced, in countries such as the UK with relatively strong egalitarian norms, thereby reducing the predictive strength of gender attitudes.…”
Section: Gender Attitude-advertisement Match Cross-nationally: Movingmentioning
confidence: 99%